Evaluation of Firewall and Load balance in Fat-Tree Topology Based on Floodlight Controller - Sarah Hashim Mohammed; Ammar Dawood Jasim (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Today it has become important to reconfigure the networks in to new form to be more manageable, scalable, dynamic and programmable. The networks recently are so inflexible and failing to deal with the required changes for the Information Technology. Software Defined Networking (SDN) is a modern paradigm that focused to change the main idea of current network infrastructure (traditional network) by breaking the chain between the data forwarding and the control planes to introduce flexible programmability network. This paper makes comparison between the performance of traditional fat-tree network and SDN fat-tree network, which found that average Round Tripe Time (RTT) in SDN fat-tree topology will decrease by 8.96% than traditional fat-tree topology. Then shows the basic operation of OpenFlow protocol that can be applied on fat-tree topology by using SDN technology and how that can be effect on the performance of network and make it more flexible to enable the SDN module applications, like load balancer and firewall for optimizing the SDN network. In this paper the physical switches are replaced by software switches in a virtual network environment and display the SDN structure in GUI, also Floodlight controller is chosen to use as the network operating system for SDN network.